Communication of dependent messages over degraded compound channels - Zhong Cheng; Yongyi Mao; Chan, Terence (2015 IEEE 14th Canadian Workshop on Information Theory (CWIT), 2015)
In the communication of source-coded messages, certain dependency structures often exist among the messages, where a source model is proposed to model arbitrary dependency structure of such kind. Under a message-dependency model, the problem of communicating dependent messages subject to certain delay constraint is formulated as the problem of maximizing the average utility at the receiver. In this paper we derive the maximal achievable utilities for superposition codes and conventional channel codes over degraded compound channels. Analytic and numerical results are presented.